보완된 문화다이아몬드 모델에 의한 패션 음악 융합 라이프스타일 브랜드 사례 분석: 아티스트 빈지노를 중심으로 - 김기창(Kee-Chang Kim); 김선영(Sun-Young Kim) (한국콘텐츠학회 논문지, 24(9), 2024)
본 논문은 보완된 문화 다이아몬드 모델을 적용하여 음악과 패션이 결합했을 때, 새로운 창조물이 어떻게 문화적 영향력을 가지게 되는지를 내용 분석 방법론을 활용하여 분석하였다. 연구 대상은 한국의 힙합 아티스트 ‘빈지노’와 아트스튜디오 ‘아이앱 스튜디오’ 간의 협업 사례이며, 연구 결과는 다음과 같다. 첫째, 문화적 객체(Cultural Object)의 관점에서, 빈지노는 아이앱 스튜디오와의 협업으로 제작된 아트워크를 통해 음악적 이야기와 감정을 시각적으로 재해석함으로써 팬들에게 다양한 해석의 기회를 제공한다. 둘째, 창조자(Creator)의 관점에서 빈지노의 음악적 정체성과 스튜디오의 시각적 전문성이 결합되어 창조자로서의 경계를 확장한다. 셋째, 수용자(Receiver)의 관점에서 팬들은 아이앱 스튜디오의 의류를 착용하고 빈지노의 콘서트에 참여함으로써 음악과 패션의 결합을 통한 개인적 표현과 소셜 미디어와 같은 디지털 플랫폼을 통해 문화적 객체를 소비하고 공유한다. 넷째, 사회적 맥락(Society Environment)의 관점에서 MZ세대를 중심으로 한 고가 명품 소비는 아이앱 스튜디오의 프리미엄 가격 전략과 일치한다. 또한 디지털 기술을 중심으로 한 SNS 플랫폼 사회로 전환되면서, 창조자와 수용자 모두 문화적 객체를 SNS에 활발히 홍보한다. 분배(Distribution)의 관점에서 빈지노와 아이앱 스튜디오는 다양한 유통 채널과 디지털 기술을 활용해 전 세계적으로 접근성을 높이고, 문화적 자본의 재분배를 통해 새로운 문화적 자산을 창출하며, 사회적 지위와 시장 내 영향력을 확장한다. 본 연구는 음악과 패션의 융합 등 창의적 협업의 중요성과 향후 음악 저작물 활용 확대 및 마케팅 전략에 대한 시사점을 제공한다. This study applies the Complementary Cultural Diamond Model to analyze how the collaboration between Korean hip-hop artist Beenzino and art studio IAB Studio transforms music into a cultural asset, focusing on the impact of combining music and fashion. The findings are as follows: First, from the Cultural Object perspective, Beenzino reinterprets musical stories and emotions visually through artwork created with IAB Studio, offering fans diverse interpretations. Second, from the Creator perspective, the combination of Beenzino’s musical identity and the studio’s visual expertise enriches the emotional expression of music, expanding the boundaries of creativity. Third, from the Receiver perspective, fans engage in personal expression and cultural experience by wearing IAB Studio’s clothing and attending Beenzino’s concerts, blending music and fashion. Fourth, from the Social World perspective, the creative work of Beenzino and IAB Studio mediates self-expression and self-realization among modern youth, enhancing global consumer connection through digital media. Lastly, from the Distribution perspective, Beenzino and IAB Studio leverage diverse distribution channels and digital technology to enhance global accessibility, providing consumers with emotional experiences that boost brand loyalty. Their creations redistribute cultural capital, generating new cultural assets and expanding their social status and market influence. This study highlights the impact of music and fashion fusion on the cultural industry, emphasizing the importance of creative collaboration and providing insights for expanding the use of music works and marketing strategies. KCI Citation Count: 0